Government Size, Trade Openness, and Output Volatility: A Case of Fully Integrated Economies - Eiji Fujii (Center for Economic Studies and ifo Institute (CESifo), 2015)
Government is often considered the safe sector of an open economy that provides households with insurance against external risk exposure. Among highly integrated economies, however, households should be able to exploit common financial markets to insure themselves. In this paper we examine the relationship between government size, trade openness, and output volatility across fully integrated economies using Japan's regional income accounting and public finance data. The contributions of the government- and market-based insurances to inter-regional risk sharing are also estimated. The empirical results reveal some unique aspects of the state-market interactions under full economic integration with vertical fiscal imbalance.
Keywords: H10; H70; F40; 330; government size; output volatility; risk-sharing; trade openness; vertical fiscal imbalance